Lichen community response to different management situations in Cerro Colorado protected forest (Cordoba, Argentina) - Quiroga, Gonzalo; Estrabou, Cecilia; Rodríguez, Juan Manuel (Lazaroa, 2009)
The conservation of native forests is an essential component for the maintenance of the biodiversity that they sustain, including lichens, which are good indicators of changes in the forest. These are sensitive to the changes of light, humidity, temperature and availability of nutrients produced by the deforestation and other processes of change in the forest. In order to know the response of the lichen communities to forest disturbance, we did an analysis of the community in two forest units with different management situations.We made a phytosociological table of the lichen community and a PCA analysis, and then evaluated the reproductive strategies of the species in each area. We selected the samples at random with a total of sixty phorophyte, in which the total coverage of the species was accounted on a 30x30 cm grid. We determined 36 species within twenty genera, with the exception of crustose lichens that we did not determine at specific level and considered as a group. Two different lichen communities are found, an “A” community dominated by Canoparmelia crozalsiana, of the forest with low disturbance and another one “B” dominated by Parmotrema reticulatum of the more disturbed forest zone. The analyses of reproductive strategies shows a greater presence of species with asexual reproduction in the less disturbed area.